Washington View: Not a snapshot of public opinion but an album. (September 2015) - Ferguson, Maria
The columnist weighs in on the most recent PDK/Gallup poll. The real value of the poll, the author says, comes from looking at each response and then thinking about the connective tissue between and among them. The poll's 47-year history adds yet another layer of rich context. Uniquely, the poll provides not a snapshot of public opinion, rather an album of the emotions and opinions that help define our nation's evolving views on public education .